Research on the Impact of Perceived Interaction on User Stickiness in the Context of Tiktok E-commerce Live Broadcast -- The Mediating Role Based on Emotional Attachment - Yue Xinran; Yang Yi; Gu Xinyan; Wang Qiuxue; Chen Shiyi (SHS Web of Conferences, 2023)
COVID-19 has been recurrent for the last three years, the competition in the e-commerce live broadcast market of ‘more, faster, better and more economical’ is becoming increasingly fierce. The Tiktok app as a typical e-commerce live broadcast platform that urgently needs to improve user stickiness to stabilize traffic. Based on the survey of users, this paper explores the influencing factors of user stickiness of e-commerce live broad-cast platform according to CAC theory, and uses SPSS software to test the obtained data. Studies have shown that perceived interaction positively affects emotional attachment, and emotional attachment positively affects user stickiness, perceived interaction can be divided into user control, connectedness, responsiveness, and entertainment, emotional attachment can be divided into platform identity and platform affection. Based on the research conclusions, reasonable suggestions are put forward for e-commerce live broadcast platform.